Analysis of recall bias of information on soccer injuries in adolescents - Franciele Marques Vanderlei; Danielli Aguilar Barbosa; Aryane Flauzino Machado; Fábio do Nascimento Bastos; Luiz Carlos Marques Vanderlei; Jayme Netto Júnior; Carlos Marcelo Pastre (Universidade Estadual Paulista (UNESP), 2017)
Abstract Aims: to analyze the recall bias of injury characteristics, anthropometric variables, and training variables in a morbidity survey in adolescent soccer players for a period of four months. Method: cohort study with 198 adolescent male soccer players, divided into two parts: a prospective study over four months, followed by a retrospective study. A morbidity survey containing personal and training data, in addition to information on injuries and their characteristics (anatomical site, mechanism, nature, moment, severity, return to activities and recurrence) was administered weekly for four months, after which the questionnaire was applied again questioning the same information retrospectively for the four-month prospective study period. The data were collected through interviews addressing the occurrence of injuries and respective characteristics. Results: there were weak correlations and concordances for the recall of the occurrence of injury and all related variables. However, regarding the information relating to personal and training data, moderate correlations were observed for the variables height, time of training, weekly hours, absences, and position, as well as excellent correlations for body mass. Conclusions: we observed recall bias in all information about the characteristics of the injuries reported by adolescent soccer players.